2015
DOI: 10.1021/acs.jpcc.5b08834
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Directed Fluorescence Switching of Silver Clusters

Abstract: Silver clusters with ≲30 atoms are molecules with diverse electronic spectra and wide-ranging emission intensities. Specific cluster chromophores form within DNA strands, and we consider a DNA scaffold that transforms a pair of silver clusters. This ~20-nucleotide strand has two components, a cluster domain (S1) that stabilizes silver clusters and a recognition site (S2) that hybridizes with complementary oligonucleotides (S2C). The single-stranded S1-S2 exclusively develops clusters with violet absorption and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 67 publications
(196 reference statements)
2
46
0
Order By: Relevance
“…These assemblies have potential applications in photonics and as optical polarizers, sensors, catalysts, etc . During the interaction of noble metal NPs with biomolecules, formation of two types of nanostructures are possible: i) metal clusters are nested on the outside of the biomolecule that are arranged in external helical chains around these peptide or DNA molecules, producing plasmonic helical metal NP assemblies ( Figure ), and ii) clusters consisting of a few to tens of metals atoms that are located inside the DNA molecule, between two polynucleotide strands …”
Section: Dna‐protected Gold and Silver Npsmentioning
confidence: 99%
See 3 more Smart Citations
“…These assemblies have potential applications in photonics and as optical polarizers, sensors, catalysts, etc . During the interaction of noble metal NPs with biomolecules, formation of two types of nanostructures are possible: i) metal clusters are nested on the outside of the biomolecule that are arranged in external helical chains around these peptide or DNA molecules, producing plasmonic helical metal NP assemblies ( Figure ), and ii) clusters consisting of a few to tens of metals atoms that are located inside the DNA molecule, between two polynucleotide strands …”
Section: Dna‐protected Gold and Silver Npsmentioning
confidence: 99%
“…Different DNA sequences can lead to different clusters, potentially with different shapes. Compact silver clusters encapsulated within DNA were obtained and described by Petty and co‐workers . The cluster size was determined by mass spectroscopy to be Ag 10 .…”
Section: Dna‐protected Gold and Silver Npsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several experimental studies have indicated that silver clusters can be stabilized by the interaction with cytosine-based oligomers, [80][81][82][83] or even be encircled by a DNA hairpin loop. 42,44,56,57 For small gold clusters, on the other hand, preferential binding to purine bases has been predicted theoretically. 84 In order to rationalize these observations and to provide further insights into possible mechanisms of binding, a reliable identification of the ground-state structures of the cluster-organic aggregates and a careful analysis of the chemical nature of the bonds formed would be particularly useful.…”
Section: A Role Of Base Identitymentioning
confidence: 99%